From lab to court: Evaluating the transfer of improvements in laboratory assessments to on-court performance in collegiate basketball players - Rauch, J.; Leidersdorf, E.; Reeves, T.; Wadhi, T.; Storey, L.; Taylor, D.; Elliott, M.; De Souza, E. O.; Tricoli, V.; Lamas, L. (International Journal of Sports Science & Coaching, 2025)
This study examined how different resistance training (RT) interventions affect the transfer between laboratory and on-court measures in collegiate basketball players. After baseline laboratory (Countermovement jump (CMJ), Acceleration deceleration ability (ADA) and on-court testing (Closeout (CO), Drive and score (DS)), one men's (N = 11, 20.92 ± 1.66 years, 1.90 ± 0.1 m, 90.27 ± 11.84 kg) and women's team (N = 13, 19.08 ± 1.26 years, 1.72 ± 0.1 m, 67.58 ± 9.42 kg) were randomly assigned to strength and plyometric training (SP) or strength training only (S) for two sessions a week over six weeks during the pre-season. Mixed model analysis revealed main time effects in the CMJ: relative braking force (Nz/kg), p < 0.001; relative braking rate of force development (N·s-1·kg-1), p < 0.001; CO live: maximum deceleration (m·s-2), p = 0.003; and DS live: average deceleration (m·s-2), p < 0.001. Notably, only in SP did the confidence intervals not intersect zero, and the delta change exceeded the minimal detectable change. For the ADA, a group-by-time interaction for average deceleration (m·s-2), p = 0.015 revealed SP improvements at post compared to pre. Lastly, stepwise regressions indicated that being in the S group predicted decreased deceleration performance relative to SP in the DS live drill. Collectively, our results suggest SP training may lead to greater adaptations in braking kinetics in the CMJ and deceleration performance in the ADA. Furthermore, SP may result in greater transference to select on-court deceleration metrics.